Transformasi Kebijakan Kesehatan Digital, Implementasi dan Tantangan: Studi Sistematic Review - Lubis, Ernawati (Prodi Kesehatan Masyarakat Fakultas Kesehatan Masyarakat UIN Sumatera Utara, 2025)
Digital health transformation is growing in various countries, but the need for this to improve access and quality of global healthcare services has not been thoroughly studied. This study aims to explore digital health transformation in various countries, including policy bases, implementation methods, challenges, and the impact of implementation on improving access and quality of healthcare services. This study used a Systematic Literature Review (SLR) approach guided by the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA). The literature search was conducted through PubMed/MEDLINE, Scopus, Web of Science, ScienceDirect, and Google Scholar. Inclusion criteria were determined based on the PICOS framework, while data analysis was conducted through thematic analysis to identify policy trends, implementation successes, barriers, and impacts of digital health adoption. Findings indicate the existence of policies at the national, community, and healthcare levels, such as the WHO Global Digital Health Strategy 2020-2025, EU4Health, and interoperability guidelines (Health Level Seven, FHIR). Implementation includes eHealth in hospitals (EMR, OCS, PACS), smartphone-based mHealth, telehealth, and innovations such as the